Pendekatan Komprehensif E-Commerce Prespektif Syariah - Muhammad Nizar (Universitas Muhammadiyah Sidoarjo, 2018)
There is concern for customers who use e-commerce services especially Islamic communities in Indonesia, both from the perspective of security and shariah perspective. There are two problems arising from this online transaction, the first is the medium of internet network transactions, and the second medium of payment by credit card. This research will discuss and highlight some of the challenges related to the sustainability of services run by the government.